2015
DOI: 10.13189/ujph.2015.030206
|View full text |Cite
|
Sign up to set email alerts
|

Birth Prevalence of Overt Congenital Anomalies in Kano Metropolis: Overt Congenital Anomalies in the Kano

Abstract: Congenital anomalies are abnormalities of prenatal origin, and their prevalence varies worldwide. The objective of this study was to determine the prevalence and spectrum of overt congenital anomalies in live born neonates in selected hospitals in the Kano metropolis of North western Nigeria, as well as the associated maternal, paternal and neonatal risk factors. A descriptive study design was employed. All live born neonates in three major hospitals in Kano metropolis were prospectively studied from April 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
5
16
1
Order By: Relevance
“…In the present study, CAs observed more in males than females (60.3%-males and 39.7%-females) which is similar findings with the studies done in Nigeria (52%-males and 48%-females), 29 Pakistan (68.3%-males and 31.7%-females), 30 Ethiopia (58.5%-males and 41.5%-females). 16 Also, supported by a national population-based study conducted in the United Kingdom; the risk of any CA was 26% greater in males.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, CAs observed more in males than females (60.3%-males and 39.7%-females) which is similar findings with the studies done in Nigeria (52%-males and 48%-females), 29 Pakistan (68.3%-males and 31.7%-females), 30 Ethiopia (58.5%-males and 41.5%-females). 16 Also, supported by a national population-based study conducted in the United Kingdom; the risk of any CA was 26% greater in males.…”
Section: Discussionsupporting
confidence: 91%
“… 31 One hundred sixty-nine (84.9%) of congenital anomalies were single, while 30 (15.1%) of anomalies were multiple (more than one anomaly in one child) which is comparable with the study done in Nigeria; almost 87% of CAs were single system congenital anomaly. 28 , 29 However, different from the studies done in Egypt and Ethiopia; 69% 32 and 95.5% 16 of the infants had a single congenital anomaly, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…This finding concurs with the past study conducted in Tanzania28. Multiple pregnancies were not significantly associated with neonatal outcome unlike the past studies29,30 which reported significant relationship.…”
Section: Discussionsupporting
confidence: 90%
“…Major congenital anomalies are defined as those that, if uncorrected, could result in considerable impairment of the normal body functions or even reducing the life expectancy. Minor congenital anomalies include the anomalies that cause no disability or have no significant physical or functional effects and can be regarded as normal variants [6, 9, 10].…”
Section: Introductionmentioning
confidence: 99%